Does Side Matter? The Impact of Free Flap Harvest Laterality on Ambulatory Function in Lower Extremity Traumatic Reconstruction - Moshal, Tayla; Roohani, Idean; Stanton, Eloise W.; Zachary, Paige K.; Boudiab, Elizabeth; Lo, Jessica; Markarian, Emily; Carey, Joseph N.; Daar, David A. (Journal of Reconstructive Microsurgery, 2024)
Background Free flaps are essential for limb salvage in patients with lower extremity (LE) trauma; however, significant donor-site morbidity could impact functional outcomes. This study compares postoperative ambulatory function between contralateral and ipsilateral free flap harvest in LE traumatic reconstruction.Methods A retrospective review was performed on patients who underwent LE reconstruction at a level 1 trauma center from 2009 to 2022. Flap characteristics, injury history, and ambulatory function were collected. Flap harvest laterality was determined in relation to the injured leg. The flaps were categorized as either fasciocutaneous or those that included a muscle component (muscle/myocutaneous). Chi-squared and Mann–Whitney tests were used for statistical analysis.Results Upon review, 173 LE free flaps were performed, of which 70 (65.4%) were harvested from the ipsilateral leg and 37 (34.6%) were from the contralateral leg. Among all LE free flaps, the limb salvage rate was 97.2%, and the flap survival rate was 94.4%. Full ambulation was achieved in 37 (52.9%) patients in the ipsilateral cohort and 18 (48.6%) in the contralateral cohort (p = 0.679). The average time to full ambulation did not vary between these cohorts (p = 0.071). However, upon subanalysis of the 61 muscle/myocutaneous flaps, the ipsilateral cohort had prolonged time to full ambulation (6.4 months, interquartile range [IQR]: 4.8–13.5) compared with the contralateral one (2.3 months, IQR: 2.3 [1.0–3.9]) p = 0.007. There was no significant difference in time to full ambulation between flap harvest laterality cohorts among the fasciocutaneous flaps (p = 0.733).Conclusion Among free flaps harvested from the ipsilateral leg, fasciocutaneous flaps were associated with faster recovery to full ambulation relative to muscle/myocutaneous flaps. Since harvesting muscle or myocutaneous flaps from the ipsilateral leg may be associated with a slower recovery of ambulation, surgeons may consider harvesting from a donor site on the contralateral leg if reconstruction requires a muscle component.
Keywords: lower extremity; traumatic reconstruction; free tissue transfer